2020
DOI: 10.3390/brainsci10070448
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Age at Autism Spectrum Diagnosis in Children with Migrant and Non-Migrant Background in Austria

Abstract: This study explored (i) differences in age at Autism Spectrum Disorder (ASD) diagnosis between children with and without a migrant background in the main diagnostic centre for ASD in Upper Austria (ii) factors related to the age at diagnosis and (iii) whether specific factors differed between the two groups. A retrospective chart analysis included all children who received their first diagnosis before the age of 10 years (n = 211) between 2013 and 2018. Children with a migrant background were diagnosed 13 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 68 publications
(81 reference statements)
0
4
1
Order By: Relevance
“…The mean age at diagnosis of 69.6 months (5.8 years) in our study was close to, though slightly older than the findings of a 2021 systematic review and meta-analysis looking at 35 studies, which found the mean age of diagnosis was 60.48 months (5.4 years) [ 25 ]. Our result is also older than a 2020 Austrian study finding, which found the mean age at diagnosis was 46.7 months (3.9 years) [ 26 ].…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…The mean age at diagnosis of 69.6 months (5.8 years) in our study was close to, though slightly older than the findings of a 2021 systematic review and meta-analysis looking at 35 studies, which found the mean age of diagnosis was 60.48 months (5.4 years) [ 25 ]. Our result is also older than a 2020 Austrian study finding, which found the mean age at diagnosis was 46.7 months (3.9 years) [ 26 ].…”
Section: Discussioncontrasting
confidence: 68%
“…The fourth limitation was related to the fact that for this research, we did not collect and analyze information regarding who referred the children to our autism diagnostic program. Therefore, we cannot confirm the Austrian findings that a referral by a pediatrician was associated with an earlier diagnosis [ 26 ]. Our results could have also been influenced by our sample, including only children, thereby excluding those diagnosed with autism in adulthood.…”
Section: Discussionmentioning
confidence: 82%
“…In contrast, studies tracking patient-level data within clinics typically use small sample sizes, research networks or private clinical services. These studies have reported mixed results to suggest that child gender14–16 and symptom severity,17 parental education,18 marital status19 and a culturally and linguistically diverse (CALD) background20–22 may be associated with assessment and diagnosis delays (see also Daniels and Mandell for a review23). These mixed findings are largely specific to autism specialist assessment clinics.…”
Section: Introductionmentioning
confidence: 99%
“…This age can also identify cognitive and language scores so that more positive results can be obtained [15]. The age of 24 months is the most appropriate age for diagnosing children at risk for ASD [16], [17]. For the gender factor, there were more males than females at risk for ASD.…”
Section: Discussionmentioning
confidence: 99%